2008
DOI: 10.1073/pnas.0804276105
|View full text |Cite
|
Sign up to set email alerts
|

The oxazolidinone antibiotics perturb the ribosomal peptidyl-transferase center and effect tRNA positioning

Abstract: The oxazolidinones represent the first new class of antibiotics to enter into clinical usage within the past 30 years, but their binding site and mechanism of action has not been fully characterized. We have determined the crystal structure of the oxazolidinone linezolid bound to the Deinococcus radiodurans 50S ribosomal subunit. Linezolid binds in the A site pocket at the peptidyltransferase center of the ribosome overlapping the aminoacyl moiety of an A-site bound tRNA as well as many clinically important an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
256
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(285 citation statements)
references
References 49 publications
7
256
0
13
Order By: Relevance
“…In 2008, two reported X‐ray co‐crystal structures of linezolid bound to 50S ribosomal subunits confirmed the previously established site of action and suggested a mode of action (Figure 4). 29, 30 …”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, two reported X‐ray co‐crystal structures of linezolid bound to 50S ribosomal subunits confirmed the previously established site of action and suggested a mode of action (Figure 4). 29, 30 …”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…Specifically, linezolid binds to a pocket formed by eight RNA residues, one of which, U2585Ec, is stabilized in a distinct conformation. By stabilizing U2585Ec in a nonproductive conformation, linezolid affects the binding and/or positioning of the initiator‐tRNA and prevents the binding of tRNA at the A site, thereby halting the translation sequence (Figure 4 A) 29…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…El linezolid es un agente bacteriostático que inhibe la síntesis proteica mediante la unión a la subunidad 50S del ribosoma bacteriano interfiriendo con la correcta acomodación del N-formil-metionil-ARN de transferencia (ARNt) en el centro peptidiltransferasa (CPT) (42). La unión con la subunidad 50S se da por interacción con el ARN ribosómico (ARNr) 23S, más específicamente con ocho nucleótidos universalmente conservados (G2061, A2451, C2452, A2503, U2504, G2505, U2506 y U2585 [numeración del ribosoma de Escherichia coli]) y con las proteínas ribosómicas que se encuentran más próximas a su sitio de unión, es decir, las L3, L4 y L22.…”
Section: Resistencia a Oxazolidinonasunclassified
“…La unión con la subunidad 50S se da por interacción con el ARN ribosómico (ARNr) 23S, más específicamente con ocho nucleótidos universalmente conservados (G2061, A2451, C2452, A2503, U2504, G2505, U2506 y U2585 [numeración del ribosoma de Escherichia coli]) y con las proteínas ribosómicas que se encuentran más próximas a su sitio de unión, es decir, las L3, L4 y L22. Esta unión causa rigidez en el nucleótido U2585, el cual normalmente presenta una flexibilidad molecular que es crucial para el posicionamiento correcto del ARNt en el sitio P del CPT y, como consecuencia, el antibiótico produce una interrupción temprana de la síntesis de péptidos (42).…”
Section: Resistencia a Oxazolidinonasunclassified
“…Crystallographic studies performed over the last decade revealed the exact binding sites of a variety of such drugs (see refs.1 and 2 for review). Many natural antibiotics, as well as their clinically relevant semisynthetic derivatives, bind at the peptidyl transferase center (PTC) in the large ribosomal subunit (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Most of these compounds inhibit cell growth by interfering with peptide bond formation (15).…”
mentioning
confidence: 99%